History of the development of dress - Johnson, Ary Cordelia (My University, 1898)
Introduction: The development of dress in a nation presents a strong analogy to the progress of its people in its architecture. Both are constantly changing, blending into one another with almost complete continuity, both yielding to a form, as a rule better adapted to the surrounding conditions. Not only can the degree of dress be very closely estimated by the architecture of different ages, but this in turn by the national affairs; also, in exact proportion to a nation’s mental advance, has been the decrease of its love of mere finery and the increase of its attention to those primary elements of beauty, form, proportion, color and fitness. The degree of advancement in dress may be known by knowing the extent to which various organs have been specialized from time to time. One thing not to be forgotten in its bearing on the development of dress is style, the love of novelty and that almost universal tendency which people have to exaggerate any peculiarity for the time being considered a mark of good station in life or handsome in itself.
Citation: Johnson, Ary Cordelia. History of the development of dress. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Dress; Architecture; Advancement; History; Theses; Manuscripts (documents)